l 3x + 2 l = l 3- 2x l

We have 4 cases:

case 1:

3x + 2 = 3- 2x

Group similar terms:

5x = 1

**==> x= 1/5**

** **

Case 2:

- (3x +2) = 3-2x

-3x - 2 = 3 - 2x

==> -x = 5

**==> x= -5**

** **

Case 3:

3x + 2 = - (3-2x)

3x + 2 = -3 + 2x

==> **x= -5**

** **

Case 4:

-(3x+2) = -(3-2x)

-3x - 2 = -3 + 2x

==> -5x = -1

**==> x= 1/5**

**Then the solution is: **

**x= { 1/5, -5}**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now